Candida Albicans - Sandai, Doblin (IntechOpen, 2019)
This book highlights modern techniques of research into Candida albicans, especially in terms of emerging and emerged pathogenic Candida species. It also looks at metabolic adaptation, resistance related to environmental stress and variety of nutrients, best performing plants that inhibit Candida's activities, interaction with other microbes, antifungal immunity mechanisms, and the posttherapeutic management of fungal infections. The book is a collection of very high impact research that includes a combination of biochemical, molecular biological, and medical microbiological innovative scientific techniques. It contains fascinating information that will help readers to explore and understand why C. albicans is different from other microbes. The authors describe this significant discovery using both bioinformatic and laboratory techniques and this uniqueness is the reason why C. albicans is a successful pathogenic yeast.